2015
DOI: 10.1007/s00253-015-6700-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into methanol-stable variants of lipase T6 from Geobacillus stearothermophilus

Abstract: Enzymatic production of biodiesel by transesterification of triglycerides and alcohol, catalyzed by lipases, offers an environmentally friendly and efficient alternative to the chemically catalyzed process while using low-grade feedstocks. Methanol is utilized frequently as the alcohol in the reaction due to its reactivity and low cost. However, one of the major drawbacks of the enzymatic system is the presence of high methanol concentrations which leads to methanol-induced unfolding and inactivation of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 58 publications
3
52
0
1
Order By: Relevance
“…The crystal structure of M8 (A187C/F291C) displays a disulfide bond connecting the enzyme helix‐lid (α9, residues F177‐A192) with position 291 in the neighboring α‐helix (Figure A). Complete and continuous electron density affirms the S−S bond and the blockage of the previously described active site tunnel . In Figure B, moderate changes in secondary structure are observed, in the Cys291 α‐helix, now in the form of a helical loop.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The crystal structure of M8 (A187C/F291C) displays a disulfide bond connecting the enzyme helix‐lid (α9, residues F177‐A192) with position 291 in the neighboring α‐helix (Figure A). Complete and continuous electron density affirms the S−S bond and the blockage of the previously described active site tunnel . In Figure B, moderate changes in secondary structure are observed, in the Cys291 α‐helix, now in the form of a helical loop.…”
Section: Resultssupporting
confidence: 74%
“…The second characterization assay preformed was unfolding temperature (T m ) measurements in buffer and in 70 % methanol (resembling methanol concentration during biodiesel production). Previous studies on LipT6 showed good correlations between methanol stability and thermostability, though the opposite correlation was found to be more complex . Mutants stable in methanol were also more thermostable, but improved thermal stability did not necessarily project stability in methanol.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…To characterize the enzymes, unfolding events of the proteins were measured with a nanoDSF device by monitoring the intrinsic tryptophan fluorescence at emission wavelengths of λ =330 and 350 nm. Because the melting temperature ( T m ) of a lipase determined by differential scanning calorimetry (DSC) was identical to that obtained by nanoDSF, this technique proved to be a straightforward, simple, and highly correlative method to traditional techniques.…”
Section: Resultsmentioning
confidence: 78%